Effect of the look-up line on the gaze and head orientation of elite ice hockey players. Issue 1 (2nd January 2017) - Vickers, Joan N.; Causer, Joe; Stuart, Michael; Little, Elaine; Dukelow, Sean; Lavangie, Marc; Nigg, Sandro; Arsenault, Gina; Morton, Barry; Scott, Matt; Emery, Carolyn
Abstract: A "look-up line" (LUL) has been proposed for ice hockey, which is an orange 1 m (40′) warning line (WL) painted on the ice at the base of the boards. The LUL purports to provide an early warning to players to keep their head up prior to and as they are being checked. We determined if players looked up more on a rink with the LUL compared to a traditional Control rink. Elite offensive (O) and defensive (D) players competed 1 vs. 1, while wearing an eye tracker that recorded their quiet eye (QE) and fixation and tracking (F-T) and an electrogoniometer that measured head angle. External cameras recorded skate duration during four skate phases: P1 preparation, P2 decision-making, P3 cut to boards, P4 contact. The QE was the final fixation prior to contact between O and D as they skated towards and across the WL during P3 and P4. Skate phase durations (%) did not differ by rink or rink by position. More QE and F-T occurred on the WL on the LUL rink than on the Control. The expected increase in head angle on the LUL rink did not occur during P3 or P4. Post-hoc results also showed O and D skated further from the boards on the LUL rink, suggesting the players preferred to control the puck on white ice, rather than the orange colour of the LUL rink. More research is needed to determine if these results apply to the competitive setting.